1975
DOI: 10.1161/01.res.36.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin on the proliferation of cultured primate arterial smooth muscle cells.

Abstract: Smooth muscle cells were grown from thoracic aortas of 1-year-old monkeys (Macaca nemistrina). The effect of insulin on the proliferation of these cells was studied by comparing the growth of cells in culture medium to which insulin had been added with that of cells in basal (1% monkey serum) medium and in growth-promoting 5% monkey serum. Insulin in concentrations of 10, 100, 1,000, and 10,000 muunits/ml resulted in successively greater stimulation of growth which was highly significant (P smaller than 0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
150
2
2

Year Published

1981
1981
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(159 citation statements)
references
References 35 publications
5
150
2
2
Order By: Relevance
“…First, chronic hyperinsulinemia might elevate arterial pressure, because insulin is reported to produce trophic actions on vascular muscle that could, over time, increase vascular resistance and arterial pressure. 41 However, Tsutsu et al 42 have reported that chronically elevated plasma insulin levels in patients with insulinoma did not result in increased arterial pressure. Furthermore, arterial pressure did not fall in these patients after tumor resection.…”
Section: Arterial Pressure Responses To Insulinmentioning
confidence: 98%
“…First, chronic hyperinsulinemia might elevate arterial pressure, because insulin is reported to produce trophic actions on vascular muscle that could, over time, increase vascular resistance and arterial pressure. 41 However, Tsutsu et al 42 have reported that chronically elevated plasma insulin levels in patients with insulinoma did not result in increased arterial pressure. Furthermore, arterial pressure did not fall in these patients after tumor resection.…”
Section: Arterial Pressure Responses To Insulinmentioning
confidence: 98%
“…14,18 Obese subjects are characterized by hyperinsulinemia and insulin-resistance, and these factors could be the cause of increased blood pressure. 19 Hyperinsulinemia, could indeed increase sympathetic activity 20,21 and sodium reabsorption, 22 modify ion transport 23 卤 25 and stimulate proliferation of smooth-muscle cells, 26 mechanisms which promote and maintain high blood pressure values.…”
Section: Discussionmentioning
confidence: 99%
“…38 There are several possible mechanisms by which insulin could increase BP, including increased renal sodium absorption, 39 increased sympathetic tone 40 and hypertrophy of vascular smooth muscle increasing peripheral resistance. 41 Several studies in children and adolescents have found positive correlations between fasting insulin concentrations and SBP. 42,43 High dietary fat intake may increase insulin resistance independent of weight gain.…”
Section: Hypertension Insulin Resistance Resistin and Adiponectinmentioning
confidence: 99%